The Association between Preoperative Dry Eye Symptoms and Postoperative Discomfort in Patients Underwent Photorefractive Keratectomy - Gilad Rabina; Ingibjorg Iris Boguslavsky; Shmuel Levartovsky; Michael Mimouni; Igor Kaiserman (Journal of Ophthalmology)
Purpose. To investigate the association between preoperative dry eye symptoms on postoperative pain and discomfort after photorefractive keratectomy (PRK). Methods. A retrospective case series of 151 consecutive patients, who underwent myopic PRK in both eyes between 5/2016 and 5/2017. Patients with positive dry eye disease (DED) signs on clinical examination or with known DED were excluded. Patients underwent a subjective evaluation for dry eye symptoms using ocular surface disease index (OSDI) and modified standard patient evaluation of eye dryness (SPEED) questionnaires. One day postoperatively, the patients were evaluated again by a questionnaire of pain, discomfort, photophobia, foreign body sensation, satisfaction with vision, and frequency of usage of anesthetic drops. Results. Fifty-two patients had any preoperative dry eye symptoms (OSDI score > 0) compared to 99 nonsymptomatic patients (OSDI score of 0). Postoperatively, the symptomatic dry eye patients suffered significantly more pain than the nondry eye patients (p=0.02). Thirteen patients had a cumulated modified SPEED score >4 (moderate to severe) in comparison to 138 patients with score of 0–4 (non to mild). Patients with moderate to severe preoperative symptoms suffered more pain (p=0.006), photophobia (p=0.005), and epiphora (p=0.03). No statistically significant difference was seen in postoperative subjective visual quality (p=0.82) between the two groups. Conclusion. Preoperative dry eye symptoms may be associated with postoperative pain, epiphora, and photophobia and thus influence negatively on patient satisfaction with this procedure.